Review on strategic technology of dense connection for the future mobile network - Zhihong QIAN; Lin XIAO; Xue WANG (Tongxin xuebao)
Based on reviews of the work regarding dense connection, the strategic technologies for dense connection in the upcoming future mobile communication were illuminated.The state of the art of dense connection, including network architecture and related technologies, the transmission technology of dense connection, and the access technology of dense connection were analyzed.A flexible access network structure with verity of connection forms coexisting was proposed.Aiming at the asymmetry of uplink and downlink coverage and considering the QoS requirements of users, a dense terminal access scheme based on the uplink-and-downlink-separated network architecture was proposed.The necessity of the three-dimensional network architecture and the integration of communication and computing to meet the needs of large-scale networking and dense connection were illuminated.Based on technologies such as terahertz and block chain, the future strategic exploratory trends such as the upward extension of frequency bands and the sharing of spectrum resources were discussed and prospected.